A qualitative investigation of parental aspirations to international education in China - Wei, Y (2022)
The 2020s witnessed a scene in terms of health, international relations, and policies. This article inquires into the shifting landscape of decision to international education in the People’s Republic of China (PRC). Shuangjian and other recently enacted educational policies point to a trend in decentralization of English language and discouragement of mass liberal education in the Chinese context. While covid does not bring about a decrease in number of Chinese students studying in western countries in these two years, there is pervasive concerns surrounding health, safety, and discrimination that cloud student and parents’ decision-making. China’s world class university movement witnesses a rise in Chinese universities on global university rankings (GURs) schemes and China’s emergence as a regional education hub attracting international students. With the increasing uncertainty in pursuing an international degree and growing quality in domestic education, this article explores shifting parental aspirations for international education in Shanghai.